La responsabilidad por producto defectuoso en el derecho colombiano. (2014)
The system of liability for defective products is a result of industrialization challenges imposed to the classical liability. This article aims to outline the characteristics of this liability according to the recently issued Law 1480 of 2011 in the Colombian context, taking elements from comparative law to explain its scope and the legal background on the subject in Colombia.